Emergent Temporal Signaling in Human Trabecular Meshwork Cells: Role of TRPV4-TRPM4 Interactions - Yarishkin, Oleg; Phuong, Tam T. T.; Vazquez-Chona, Felix; Bertrand, Jacques; van Battenburg-Sherwood, Joseph; Redmon, Sarah N.; Rudzitis, Christopher N.; Lakk, Monika; Baumann, Jackson M.; Freichel, Marc; Hwang, Eun-Mi; Overby, Darryl; et al. (Frontiers in Immunology, 2022)
Trabecular meshwork (TM) cells are phagocytic cells that employ mechanotransduction to actively regulate intraocular pressure. Similar to macrophages, they express scavenger receptors and participate in antigen presentation within the immunosuppressive milieu of the anterior eye. Changes in pressure deform and compress the TM, altering their control of aqueous humor outflow but it is not known whether transducer activation shapes temporal signaling remain. The present study combines electrophysiology, histochemistry and functional imaging with gene silencing and heterologous expression to gain insight into Ca2+ signaling downstream from TRPV4 (Transient Receptor Potential Vanilloid 4), a stretch-activated polymodal cation channel. Human TM cells respond to the TRPV4 agonist GSK1016790A with fluctuations in intracellular Ca2+ concentration ([Ca2+]i) and an increase in [Na+]i. [Ca2+]i oscillations coincided with monovalent cation current that was suppressed by BAPTA, Ruthenium Red and the TRPM4 (Transient Receptor Potential Melastatin 4) channel inhibitor 9-phenanthrol. TM cells expressed TRPM4 mRNA, protein at the expected 130-150 kDa and showed punctate TRPM4 immunoreactivity at the membrane surface. Genetic silencing of TRPM4 antagonized TRPV4-evoked oscillatory signaling whereas TRPV4 and TRPM4 co-expression in HEK-293 cells reconstituted the oscillations. Membrane potential recordings suggested that TRPM4-dependent oscillations require release of Ca2+ from internal stores. 9-phenanthrol did not affect the outflow facility in mouse eyes and eyes from animals lacking TRPM4 had normal intraocular pressure. Collectively, our results show that TRPV4 activity initiates dynamic calcium signaling in TM cells by stimulating TRPM4 channels and intracellular Ca2+ release. It is possible that TRPV4-TRPM4 interactions downstream from the tensile and compressive impact of intraocular pressure contribute to homeostatic regulation and pathological remodeling within the conventional outflow pathway.